Compartimentação geomorfológica da Serra do Tepequém-RR, com base em produtos de sensoriamento remoto - Nascimento, Franzmiller Almeida (2013)
The state of Roraima is marked by a diversity of landscapes differentiated relative to other portions of the Brazilian Amazon. In this scenario stands out the landscape of the northern portion of the state, consists of units which relief can reach about 2,800 feet. Among these elevations stand out reliefs tabular morphologies with large tables with flat top, known regionally for tepuis. In this scenario, is presented with a mountain of great importance Tepequém, located in the northern portion of the state, classified by current literature as a table relief, But inside are noticeable roughness altimeter that provide a gap of over 600 feet at its top. With the advancement of current research and new technologies for mapping using GIS techniques and remote sensing images, can identify diverse landforms diversified on top of the mountain. Due to the morphological complexity of the area, this study aims to classify the landforms that make up the landscape of the Tepequém mountain by mapping units morphostructural using geoprocessing techniques and photointerpretative and with use of remote sensing images, altimetry data and field. The following procedures apply methodologies developed from analysis for the recognition of natural elements of the landscape (drainage and relief), by characterizing textural properties in optical imaging TM, LISS-III and PRISM and SAR / SIPAM sensor and interpretation of areas bounded by lines isomorphostructural, generating specific products such as thematic maps and images digitally integrated. The analysis identified morphostructural an elaborate structure in an asymmetric synclinorium with preferential NE-SW axis, with fold lower expression in his side (sinformes and antiform) and tilted fault blocks generated from normal and transcurrent faults, conditioning varied landforms on top the mountain. Among these are: a) fault scarps retreat b) steep slopes, c) residual hills NE-SW and E-W aligned d) valleys f) intermontains plains. These various forms disqualify relief tabular type to the Tepequém mountain. Understanding the processes morphostructural active in building and sustaining these landforms, it constitutes an important step in understanding the evolution of the landscape.